Shelf-life extension of traditional licorice root “sherbet” with a novel pulsed electric field processing - Akdemir Evrendilek, Gulsun; Tanriverdi, Hakan; Demir, Irem; Uzuner, Sibel (Frontiers in Food Science and Technology, 2023)
Pulsed electric field (PEF) processing of licorice root “sherbet” (LRS) by various electric field strengths (7.00, 15.50, and 24.10 kV/cm), treatment times (108, 432, and 756 µsec), and processing temperatures (6, 18, and 30°C) according to the Box–Behnken design were performed. The samples were analyzed for pH, titratable acidity, conductivity, turbidity, total reducing sugar, color (L*, a*, and b*), hue, chroma, total color difference, color intensity, color tone (yellow, red, and blue color tones), total antioxidant capacity, total phenolic substance content, and sensory properties. Results revealed that PEF processing did not adversely affect most of the physical, chemical, and sensory properties of LRS, with a maximum of 2.48, 4.04, 1.78, and 1.20 log reductions on the initial total mesophilic aerobic bacteria, total mold and yeast, Bacillus circulans, and Candida tropicalis. The response variable modeled for the PEF was found to be conductivity, with the optimum processing conditions of 6.90 kV/cm, 756.00 µs, and 7.48°C. After that, the samples were stored at 4°C and 22°C for shelf-life studies. Control samples at 4°C and 22°C were spoiled on the fifth and second days, whereas PEF-treated samples stored at 4°C began to deteriorate after the 40th day and the samples stored at 22°C after the 30th day, respectively. It was revealed that PEF is a suitable process to extend the shelf-life of licorice “sherbet” with preservation of physicochemical and sensory properties.